Loan Loss Provisioning Rules, Procyclicality, and Financial Volatility - Agénor, Pierre-Richard; Zilberman, Roy (Journal of Banking & Finance, 2015)
Interactions between loan-loss provisioning regimes and business cycle fluctuations are studied in a dynamic stochastic general equilibrium model with credit market imperfections. With a specific provisioning system, provisions are triggered by past due payments. With a dynamic system, both past due payments and expected losses over the whole business cycle are accounted for, and provisions are smoothed over the cycle. Numerical experiments with a parameterized version of the model show that a dynamic provisioning regime can be highly effective in mitigating procyclicality of the financial system. The results also indicate that the combination of a credit gap-augmented Taylor rule and a dynamic provisioning system with full smoothing may be the most effective way to mitigate real and financial volatility associated with financial shocks.